Negative electrode material and secondary battery

CN122968258APending Publication Date: 2026-10-23BTR NEW MATERIAL GRP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510513984.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-22
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

然而,硅负极材料在脱嵌锂过程中存在显著的体积膨胀问题,其体积膨胀率最大可达300%

Benefits of technology

[0018]在如上所提供的负极材料的方案中,本申请实施方式的负极材料具有核壳结构,内核为多孔材料,外壳至少包括第一包覆层,多孔材料丰富的孔洞能够有利于缓解负极材料的体积膨胀,有效吸收因体积膨胀产生的应力,还能够提供充足的储锂位点,提高负极材料的储锂性能;第一包覆层能够避免电解液与内核的直接接触,减少副反应;同时通过控制负极材料满足5≤P×H≤60,改善了负极材料的耐膨胀能力。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122968258A_ABST
    Figure CN122968258A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of battery negative electrode materials. The application discloses a negative electrode material and a secondary battery, the negative electrode material comprising a porous material and a first coating layer, the first coating layer being coated on at least part of the surface of the porous material, and the negative electrode material satisfying 5<=P*H<=60; wherein P represents the porosity of the negative electrode material, and H represents the thickness of the first coating layer. According to the scheme of the application, the swelling resistance of the negative electrode material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application generally relates to the field of battery anode material technology. More specifically, this application relates to an anode material and a secondary battery. Background Technology

[0002] In the field of lithium-ion batteries, silicon anode materials have become an ideal choice for next-generation lithium-ion batteries due to their high theoretical specific capacity. However, silicon anode materials suffer from significant volume expansion during lithium insertion / extraction, with a volume expansion rate reaching up to 300%. This problem leads to a series of adverse consequences: silicon particle pulverization, damaging the electrode structure; increased internal stress in the battery, potentially causing electrode breakage. These issues not only severely affect the battery's cycle life but also threaten its safety performance, greatly limiting the large-scale application of silicon anode materials.

[0003] Therefore, developing a silicon anode material with low expansion and long cycle life has become a key issue that urgently needs to be addressed in this field. Summary of the Invention

[0004] In order to at least solve one or more of the technical problems mentioned above, this application proposes a negative electrode material, a method for preparing the negative electrode material, and a scheme for a secondary battery in several aspects.

[0005] In a first aspect, this application provides a negative electrode material comprising a porous material and a first coating layer, the first coating layer being located on at least a portion of the surface of the porous material, and the negative electrode material satisfying: 5 ≤ P × H ≤ 60; where P represents the porosity of the negative electrode material and H represents the thickness of the first coating layer.

[0006] In some embodiments, the negative electrode material also satisfies at least one of the following characteristics: (1) the porosity P of the negative electrode material is 5% to 50%; (2) the thickness H of the first coating layer is 20 nm to 400 nm; (3) the first coating layer comprises a transition metal nitride.

[0007] In other embodiments, the first coating layer comprises a transition metal nitride, which includes at least one of titanium nitride, vanadium nitride, tungsten nitride, molybdenum nitride, zirconium nitride, chromium nitride, tantalum nitride, niobium nitride, hafnium nitride, and manganese nitride.

[0008] In other embodiments, the negative electrode material also satisfies at least one of the following characteristics: (1) the porosity P of the negative electrode material is 10% to 30%; (2) the thickness H of the first coating layer is 50 nm to 200 nm.

[0009] In some embodiments, the negative electrode material further includes a second coating layer that covers at least a portion of the surface of the first coating layer.

[0010] In some other embodiments, the negative electrode material also satisfies at least one of the following characteristics: (1) the second coating layer comprises at least one of carbon material, metal oxide and phosphate; (2) the thickness of the second coating layer is 50 nm to 1000 nm; (3) the mass content of the first coating layer in the negative electrode material is 2% to 10%; (4) the second coating layer comprises carbon material, and the mass content of carbon element in the negative electrode material is 10% to 40%.

[0011] In some embodiments, the negative electrode material further satisfies at least one of the following characteristics: (1) the median particle size of the negative electrode material is 1 μm to 22 μm; (2) the specific surface area of ​​the negative electrode material is 1 m². 2 / g~20m 2 / g; (3) The compaction density of the negative electrode material is 0.5 g / cm³. 3 ~3.0g / cm 3 (4) The average pore size of the negative electrode material is 1.5 nm to 35 nm; (5) The total pore volume of the negative electrode material is 0.002 cm³. 3 / g~0.1cm 3 / g.

[0012] In other embodiments, the porous material further satisfies at least one of the following characteristics: (1) the average particle size of the porous material is 1 μm to 20 μm; (2) the average pore size of the porous material is 2 nm to 200 nm; (3) the volume ratio of mesopores to macropores in the porous material is 1 to 10; (4) the pore volume of the porous material is 0.1 cm³. 3 / g~0.8cm 3 / g; (5) The specific surface area of ​​the porous material is 100m². 2 / g~450m 2 / g.

[0013] In some other embodiments, the porous material also satisfies at least one of the following characteristics: (1) the porous material comprises a porous silicon material, wherein the mass content of silicon in the negative electrode material is 50% to 80%; (2) the porous silicon material comprises at least one of elemental silicon, silicon oxide, and silicate; (3) the purity of the porous silicon material is greater than or equal to 99%; and (4) the size of the grains of the porous silicon material on the (111) crystal plane is less than or equal to 10 nm.

[0014] In a second aspect, this application provides a method for preparing a negative electrode material, comprising: subjecting a mixture of a porous material and a transition metal salt solution to a hydrothermal reaction to obtain an intermediate material, wherein the concentration of the transition metal salt solution is 0.5 mol / L to 6 mol / L, and the hydrothermal reaction time is 1 h to 4 h; introducing a nitrogen source into the intermediate material to perform nitriding treatment to obtain a negative electrode material coated with a first coating layer.

[0015] In some embodiments, prior to the hydrothermal reaction, the preparation method further includes: heat-treating the matrix precursor to obtain a matrix intermediate; mixing the matrix intermediate with a hydrofluoric acid solution to etch the matrix intermediate to obtain the porous material, wherein the concentration of the hydrofluoric acid solution is 0.5 mol / L to 4 mol / L, and the etching time of the etching treatment is 1 h to 3 h.

[0016] In other embodiments, the preparation method further includes: performing a second coating treatment on the negative electrode material coated with the first coating layer to obtain a negative electrode material including the second coating layer.

[0017] In a third aspect, this application provides a secondary battery comprising the negative electrode material described in any one of the first aspects of this application or the negative electrode material prepared according to any one of the preparation methods described in the second aspect of this application.

[0018] In the above-mentioned anode material solutions, the anode material of this application embodiment has a core-shell structure, with the core being a porous material and the outer shell including at least a first coating layer. The abundant pores of the porous material can help alleviate the volume expansion of the anode material, effectively absorb the stress caused by the volume expansion, and also provide sufficient lithium storage sites, thereby improving the lithium storage performance of the anode material. The first coating layer can prevent the electrolyte from directly contacting the core, reducing side reactions. At the same time, by controlling the anode material to satisfy 5≤P×H≤60, the expansion resistance of the anode material is improved. Attached Figure Description

[0019] The above and other objects, features, and advantages of exemplary embodiments of this application will become readily understood by reading the following detailed description with reference to the accompanying drawings. In the drawings, several embodiments of this application are illustrated by way of example and not limitation, and the same or corresponding reference numerals denote the same or corresponding parts, wherein:

[0020] Figure 1 A schematic diagram of a battery in a discharged state, i.e., during operation, is shown.

[0021] Figure 2 An exemplary flowchart of a method for preparing a negative electrode material according to some embodiments of this application is shown;

[0022] Figure 3 The XRD pattern of the negative electrode material of Example 1 is shown;

[0023] Figure 4 An SEM image of the negative electrode material of Example 1 is shown. Detailed Implementation

[0024] The technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some, not all, of the embodiments of this application. All other embodiments obtained by those skilled in the art based on the embodiments of this application without creative effort are within the scope of protection of this application.

[0025] It should be understood that the terms "comprising" and "including" as used in the specification and claims of this application indicate the presence of the described features, integrals, steps, operations, elements and / or components, but do not exclude the presence or addition of one or more other features, integrals, steps, operations, elements, components and / or collections thereof.

[0026] It should also be understood that the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the application. As used in this specification and claims, the singular forms “a,” “an,” and “the” are intended to include the plural forms unless the context clearly indicates otherwise. It should also be understood that the term “and / or” as used in this specification and claims refers to any combination and all possible combinations of one or more of the associated listed items, and includes such combinations.

[0027] As used in this specification and claims, the term "if" may be interpreted, depending on the context, as "when," "once," "in response to determination," or "in response to detection." Similarly, the phrase "if determined" or "if [described condition or event] is detected" may be interpreted, depending on the context, as "once determined," "in response to determination," "once [described condition or event] is detected," or "in response to detection of [described condition or event]."

[0028] The specific embodiments of this application are described in detail below with reference to the accompanying drawings. Unless otherwise specified, the materials, reagents and equipment used in the embodiments of this application are obtained through conventional commercial channels.

[0029] Figure 1 This diagram shows a battery in a discharged state, i.e., during operation. Figure 1As shown, the electrode assembly includes a positive electrode 110, a negative electrode 120, and a separator 130, with the separator 130 disposed between the positive electrode 110 and the negative electrode 120. The electrode assembly can be a stacked structure, formed by alternately stacking the positive electrode 110, the separator 130, and the negative electrode 120. In other embodiments, the electrode assembly can also be a wound structure, formed by sequentially stacking and winding the positive electrode, the separator, and the negative electrode.

[0030] Positive electrode tablets:

[0031] The positive electrode 110 includes a positive current collector 111 and a positive active layer 112 disposed on at least one surface of the positive current collector. The positive current collector 111 can be aluminum foil or nickel foil, or any composite current collector disclosed in the prior art, such as, but not limited to, a current collector formed by combining a conductive foil and a polymer substrate. The positive active layer 112 contains a positive active material, which includes compounds that reversibly insert and extract metal ions. In some embodiments, the positive active material may include lithium transition metal composite oxides, sodium transition metal composite oxides, etc. The lithium transition metal composite oxide contains lithium and at least one element selected from cobalt, manganese, and nickel. In some embodiments, the positive active material may include, but is not limited to, lithium cobalt oxide (LiCoO2), lithium nickel manganese cobalt ternary materials (NCM), lithium manganese oxide (LiMn2O4), and lithium nickel manganese oxide (LiNi). 0.5 Mn 1.5 At least one of the following: O4 or lithium iron phosphate (LiFePO4).

[0032] Negative electrode plate:

[0033] The negative electrode 120 includes a negative electrode current collector 121 and a negative electrode active material layer 122 disposed on at least one surface of the negative electrode current collector. The negative electrode current collector 121 can be at least one of copper foil, nickel foil, stainless steel foil, titanium foil, or carbon-based current collectors, or any composite current collector disclosed in the prior art, such as, but not limited to, current collectors formed by combining the aforementioned conductive foil and polymer substrate. The negative electrode active material layer 122 includes the negative electrode material described below.

[0034] During battery operation, i.e. when the battery is in a discharge state, metal ions 140 (e.g., lithium ions) in the negative electrode are released from the lattice of the negative electrode material, pass through the electrolyte / electrolyte through the separator 130, and are embedded in the lattice of the positive electrode material.

[0035] Conversely, when the battery is charged by applying an external circuit, the oxidation of the positive electrode material causes metal ions (such as lithium ions) in the positive electrode to be released from the lattice of the positive electrode material, pass through the electrolyte / electrolyte through the separator 130, and move to the negative electrode; at the same time, the negative electrode material undergoes a reduction reaction, causing metal ions to be embedded in the lattice of the negative electrode material.

[0036] As metal ions move back and forth between the positive and negative electrodes, the battery can achieve the discharge and charge process in thousands of cycles.

[0037] In a first aspect, this application provides a negative electrode material comprising a porous material and a first coating layer, the first coating layer being located on at least a portion of the surface of the porous material, and the negative electrode material satisfying: 5 ≤ P × H ≤ 60; where P represents the porosity of the negative electrode material and H represents the thickness of the first coating layer.

[0038] The porous material serves as the core of the negative electrode material, providing space for the intercalation of metal ions. The first coating layer is located on at least a portion of the surface of the porous material, and can cover a portion or the entire surface of the porous material, thereby protecting the porous material and improving its performance.

[0039] In anode materials, porosity refers to the ratio of the volume of pores within the material to the total volume of the material, usually expressed as a percentage (%). It is an important parameter for measuring the size and distribution of pore spaces within the material. The thickness of the first coating layer refers to the distance from the surface of the porous material to the outer surface of the first coating layer, usually measured in nanometers (nm). In some embodiments, the thickness of the first coating layer can be the average thickness of the first coating layer.

[0040] The negative electrode material satisfies the condition: 5 ≤ P × H ≤ 60. For example, P × H can be 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, or other values ​​within the range of 5 to 60. By controlling the product of the porosity P of the negative electrode material and the thickness H of the first coating layer to be within the range of 5 to 60, the expansion resistance and electrochemical performance of the negative electrode material can be improved. The inventors have also discovered that within the range of 5 ≤ P × H ≤ 60, the expansion resistance of the negative electrode material increases with the increase of the P × H value.

[0041] If P×H < 5, it indicates that the porosity of the negative electrode material is small and / or the thickness of the first coating layer is thin. Smaller porosity means a smaller volume available for buffering; a thinner first coating layer results in lower structural strength of the negative electrode material, making it less resistant to volume expansion. During battery charging and discharging, the negative electrode material is easily damaged by volume expansion, leading to rapid capacity decay and shortened cycle life.

[0042] If P×H > 60, it indicates that the porosity of the negative electrode material is relatively high and / or the thickness of the first coating layer is relatively thick. Higher porosity in the negative electrode material may affect its core strength; a thicker first coating layer can lead to difficulties in the insertion / extraction of metal ions (e.g., lithium ions), resulting in a reduction in the battery's capacity and rate performance.

[0043] In some embodiments, the first coating layer comprises a transition metal nitride. In other embodiments, the transition metal nitride comprises at least one of titanium nitride, vanadium nitride, tungsten nitride, molybdenum nitride, zirconium nitride, chromium nitride, tantalum nitride, niobium nitride, hafnium nitride, and manganese nitride. Compared to other metal nitrides or metal oxides, transition metal nitrides possess higher structural strength, effectively protecting and supporting the core structure, ensuring core structural stability, enabling the anode material to effectively resist stress changes caused by volume expansion, reducing the risk of anode material particle breakage and pulverization, and improving the cycle life of the battery prepared from the anode material.

[0044] In other embodiments, the porosity P of the negative electrode material is 5% to 50%. Exemplarily, the porosity P of the negative electrode material can be 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, or other values ​​within the range of 5% to 50%. A porosity P within the range of 5% to 50% provides sufficient space in the negative electrode material to buffer the volume changes generated during lithium-ion insertion and extraction. This buffering effect is more ideal when the porosity is in the preferred range of 10% to 30%. Abundant pores provide sufficient space for the porous material to expand in volume, reducing interparticle compression, effectively reducing the risk of particle pulverization, and thus maintaining the integrity of the electrode structure prepared from the negative electrode material. Simultaneously, a suitable porosity can also increase the contact area between the material and the electrolyte, which is beneficial for lithium-ion transport and improves the charge-discharge performance of the battery.

[0045] If the porosity of the negative electrode material is too small (e.g., P < 5%), the volume available for buffering core expansion is too small. The porous material experiences greater constraint during volume expansion, easily leading to particle breakage and damage to the electrode structure. This results in rapid capacity decay and shortened cycle life. Smaller porosity also reduces the contact area between the material and the electrolyte, hindering lithium-ion transport and lowering charge / discharge efficiency. Conversely, if the porosity of the negative electrode material is too large (e.g., P > 50%), while the ability to buffer core expansion is enhanced, the structural strength of the negative electrode material decreases significantly. During charge / discharge, the electrode structure is prone to collapse, affecting battery stability. Furthermore, excessive pores occupy a large space, reducing the loading of active material and lowering the battery's energy density.

[0046] In some other embodiments, the thickness H of the first coating layer is 20 nm to 400 nm. Exemplarily, the thickness H of the first coating layer can be 20 nm, 50 nm, 80 nm, 100 nm, 120 nm, 150 nm, 180 nm, 200 nm, 220 nm, 250 nm, 280 nm, 300 nm, 320 nm, 350 nm, 380 nm, 400 nm, or other values ​​within the range of 20 nm to 400 nm. When the thickness of the first coating layer is within the range of 20 nm to 400 nm, it has high structural strength, can withstand the stress generated by the volume expansion of the negative electrode material core, reduces the possibility of core structure damage, enhances the negative electrode material's resistance to volume expansion, and improves the cycle life of the battery made from the negative electrode material. Simultaneously, a suitable thickness will not excessively hinder the insertion and extraction of lithium ions, ensuring the battery's capacity and rate performance. When the thickness H of the first coating layer is preferably in the range of 50nm to 200nm, the ability to resist volume expansion and the impact on lithium-ion insertion / extraction are better balanced, ensuring the overall performance of the battery.

[0047] If the thickness of the first coating layer is too small (e.g., less than 20 nm), it may result in insufficient structural strength, making it difficult to effectively support and protect the porous material core. When the porous material core expands in volume, the first coating layer is prone to cracking, failing to perform its intended protective function, leading to the breakage of the anode material particles and a decrease in battery performance. If the thickness of the first coating layer is too large (e.g., greater than 400 nm), it will severely hinder the insertion and extraction of lithium ions, significantly reducing the capacity and rate performance of the battery prepared from the anode material, thus failing to meet the requirements of practical applications.

[0048] In other embodiments, the negative electrode material further includes a second coating layer that covers at least a portion of the surface of the first coating layer. The second coating layer covering at least a portion of the surface of the first coating layer may cover a portion of the surface of the first coating layer or the entire surface of the first coating layer. That is, the first coating layer is closer to the surface of the porous material than the second coating layer. In this embodiment, the outer shell of the negative electrode material includes two coating layers, which can provide better protection for the porous material core.

[0049] In some other embodiments, the second coating layer includes at least one of carbon materials, metal oxides, and phosphates.

[0050] In some embodiments, the second coating layer includes a carbon material, which may include at least one of crystalline carbon, amorphous carbon, hard carbon, or soft carbon. Hard carbon refers to carbon materials that cannot be fully graphitized even at temperatures above 2500°C. Soft carbon refers to carbon materials that can be fully graphitized even at temperatures above 2500°C. Because carbon materials possess excellent electrical conductivity, including a carbon material in the second coating layer can help improve the conductivity of the negative electrode material. Simultaneously, the carbon material coating layer has a certain structural strength, which is beneficial for further improving the cycle performance of the material.

[0051] In other embodiments, the second coating layer comprises a metal oxide, which may include at least one oxide selected from Sn, Ge, Fe, Cu, Ti, Na, Mg, Al, Ca, and Zn. Metal oxides possess good mechanical strength, which can improve the structural strength of the second coating layer, thereby contributing to improved structural strength of the negative electrode material particles.

[0052] In some other embodiments, the second coating layer comprises a phosphate, which may include at least one of magnesium phosphate, calcium phosphate, aluminum phosphate, titanium phosphate, chromium phosphate, cobalt phosphate, nickel phosphate, germanium phosphate, zirconium phosphate, niobium phosphate, molybdenum phosphate, tantalum phosphate, tungsten phosphate, and lanthanum phosphate. Phosphates have good conductivity and low cost, and can improve the conductivity of the negative electrode material.

[0053] In some embodiments, the thickness of the second coating layer is 50 nm to 1000 nm. Exemplarily, the thickness of the second coating layer can be 50 nm, 100 nm, 150 nm, 200 nm, 250 nm, 300 nm, 350 nm, 400 nm, 450 nm, 500 nm, 550 nm, 600 nm, 650 nm, 700 nm, 750 nm, 800 nm, 850 nm, 900 nm, 950 nm, 1000 nm, or other values ​​within the range of 50 nm to 1000 nm. A second coating layer thickness within the range of 50 nm to 1000 nm can effectively improve the overall performance of the negative electrode material. Taking a carbon material as an example, a suitable thickness can enhance the conductivity of the negative electrode material and improve the charge and discharge efficiency of the battery prepared from the negative electrode material. Meanwhile, the second coating layer also has a certain structural strength, which can further protect the internal first coating layer and porous materials, reduce the occurrence of side reactions between the negative electrode material and the electrolyte, and improve the cycle performance of the battery made of the negative electrode material.

[0054] If the thickness of the second coating layer is too small (e.g., less than 50 nm), its protective and performance-enhancing effects on the first coating layer and porous materials are limited, failing to fully realize its functions of conductivity and structural stability enhancement. If the thickness of the second coating layer is too large (e.g., greater than 1000 nm), it increases the internal resistance of the negative electrode material, affecting the lithium-ion transport rate and reducing the battery's charge-discharge performance. Furthermore, an excessively thick coating layer may increase material costs and is prone to uneven coating during the fabrication process, affecting product quality.

[0055] In some embodiments, the average pore size of the negative electrode material is from 1.5 nm to 35 nm. For example, the average pore size of the negative electrode material can be 1.5 nm, 3 nm, 5 nm, 7 nm, 8 nm, 9 nm, 10 nm, 15 nm, 18 nm, 25 nm, 35 nm, or any value within the range of any two of the above values. Pores in the negative electrode material with an average pore size within the above range provide buffer space for core expansion, which helps to reduce the expansion effect of the core.

[0056] In some embodiments, the total pore volume of the negative electrode material is 0.002 cm³. 3 / g to 0.1cm 3 / g. For example, the total pore volume of the negative electrode material can be 0.002 cm³. 3 / g, 0.006cm 3 / g, 0.007cm 3 / g, 0.008cm 3 / g, 0.009cm 3 / g, 0.010cm 3 / g, 0.015cm 3 / g, 0.050cm 3 / g, 0.070cm 3 / g, 0.085cm 3 / g, 0.1cm 3 / g or any value within the range of any two of the above values. Controlling the total pore volume of the negative electrode material within the above range is beneficial for ensuring that the negative electrode material has sufficient pores, providing buffer space for core expansion, and thus reducing the core expansion effect.

[0057] In other embodiments, the mass content of the first coating layer in the negative electrode material is 2% to 10%. Exemplarily, the mass content of the first coating layer in the negative electrode material can be 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, or other values ​​within the range of 2% to 10%.

[0058] In some other embodiments, the second coating layer comprises a carbon material, wherein the mass content of carbon in the negative electrode material is 10% to 40%. Exemplarily, the mass content of carbon in the negative electrode material can be 10%, 12%, 14%, 15%, 16%, 18%, 20%, 22%, 24%, 25%, 26%, 28%, 30%, 32%, 34%, 35%, 36%, 38%, 40%, or other values ​​within the range of 10% to 40%.

[0059] In some embodiments, the median particle size of the negative electrode material is 1 μm to 22 μm. Exemplarily, the median particle size of the negative electrode material can be 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, 20 μm, 21 μm, 22 μm, or other values ​​within the range of 1 μm to 22 μm. Controlling the median particle size of the negative electrode material within the above range is beneficial for improving the cycle performance of the negative electrode material.

[0060] In other embodiments, the specific surface area of ​​the negative electrode material is 1 m². 2 / g~20m 2 / g. For example, the specific surface area of ​​the negative electrode material can be 1m². 2 / g、2m 2 / g、3m 2 / g、4m 2 / g、5m 2 / g、6m 2 / g、7m 2 / g、8m 2 / g、9m 2 / g, 10m 2 / g、11m 2 / g、12m 2 / g、13m 2 / g、14m 2 / g, 15m 2 / g, 16m 2 / g、17m 2 / g、18m 2 / g、19m 2 / g、20m 2 / g, or 1m 2 / g~20m 2 Other values ​​within the / g range.

[0061] The specific surface area of ​​the negative electrode material affects the contact area between the negative electrode material and the electrolyte. Within the aforementioned range, the specific surface area of ​​the negative electrode material can reduce the amount of lithium ions consumed by the SEI film formed during the first charge-discharge cycle of the lithium-ion battery, thus reducing irreversible capacity loss. An excessively small specific surface area means insufficient contact area between the negative electrode material and the electrolyte, potentially leading to reduced lithium-ion transport efficiency. When the specific surface area of ​​the negative electrode material is large, the SEI film on the surface of the negative electrode material will consume excessive lithium salt, and the volume effect can easily cause electro-deposition between particles, resulting in a decrease in the battery's reversible capacity and coulombic efficiency. Therefore, the negative electrode material in this embodiment has a small specific surface area, which is beneficial for improving the battery's first discharge capacity and first coulombic efficiency.

[0062] In some other embodiments, the compaction density of the negative electrode material is 0.5 g / cm³. 3 ~3.0g / cm 3 For example, the compaction density of the negative electrode material is 0.5 g / cm³. 3 0.6g / cm 3 0.8g / cm 3 1.0g / cm 3 1.2g / cm 3 1.4g / cm 3 1.5g / cm 3 1.6g / cm 3 1.8g / cm 3 2.0g / cm 3 2.2g / cm 3 2.4g / cm 3 2.5g / cm 3 2.6g / cm 3 2.8g / cm 3 3.0g / cm 3 etc., or 0.5g / cm 3 ~3.0g / cm 3 Other values ​​within the specified range. Compacted density refers to the density of a material during the compaction process, and is commonly used to describe the compactness of battery materials. A higher compacted density generally indicates a higher capacity of the battery material; therefore, compacted density is also considered one of the reference indicators for material energy density. Controlling the compacted density within the above-mentioned range is beneficial for improving the capacity of the negative electrode material. If the compacted density is too low, the capacity of the negative electrode material will be too low. If the compacted density is too high, it may increase the internal resistance of the battery, thereby affecting the battery's charge and discharge efficiency.

[0063] In some embodiments, the porosity of the porous material can be 10% to 60%, which helps to ensure the porosity of the negative electrode material. In some preferred embodiments, the porosity of the porous material can be 20% to 40%.

[0064] In some other embodiments, the average particle size of the porous material is 1 μm to 20 μm. Exemplarily, the average particle size of the porous material can be 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, 20 μm, etc., or other values ​​in the range of 1 μm to 20 μm.

[0065] In some embodiments, the average pore size of the porous material is 2 nm to 200 nm. An appropriate pore size provides an effective transport path for lithium ions, thereby improving lithium ion insertion / extraction kinetics and enhancing battery charge / discharge performance. Conversely, excessively small pore sizes may restrict lithium ion transport, leading to increased lithium ion diffusion resistance during charge / discharge and thus reducing the battery's rate performance. Excessively large pore sizes may reduce the structural stability of the negative electrode material, making it prone to breakage and pulverization during charge / discharge, thus affecting the battery's cycle life.

[0066] In other embodiments, the volume ratio of mesopores to macropores in the porous material is 1 to 10. Exemplarily, this volume ratio can be 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, or other values ​​within the range of 1 to 10. Generally, pores with a diameter of 2 nanometers to 50 nanometers (nm) are called mesopores, while pores larger than 50 nanometers are called macropores. A mesopore to macropore volume ratio in the range of 1 to 10 in porous materials can balance the requirements of lithium-ion transport, electrolyte-electrode contact, volume expansion buffering, and lithium storage sites, thereby optimizing the electrochemical performance of the anode material.

[0067] When the volume ratio of mesopores to macropores in a porous material is less than 1, it means that the volume of macropores is dominant. This may reduce the structural stability of the negative electrode material, making it prone to breakage and cracking during the pressing process when the negative electrode material is made into an electrode sheet, resulting in poor processing performance. When the volume ratio of mesopores to macropores in a porous material is greater than 10, it means that the volume of mesopores is too large, which may restrict the transport of lithium ions. Because the pore size of mesopores is small, it leads to increased resistance to lithium ion diffusion during charging and discharging, thereby reducing the rate performance of the battery.

[0068] In some other embodiments, the pore volume of the porous material is 0.1 cm³. 3 / g~0.8cm 3 / g. For example, the pore volume of the porous material can be 0.1 cm³. 3 / g, 0.15cm 3 / g, 0.2cm 3 / g, 0.25cm 3 / g, 0.3cm 3 / g, 0.35cm 3 / g, 0.4cm 3 / g, 0.45cm 3 / g, 0.5cm 3 / g, 0.55cm 3 / g, 0.6cm 3 / g, 0.65cm 3 / g, 0.7cm 3 / g, 0.75cm 3 / g, 0.8cm 3 / g, or 0.1cm 3 / g~0.8cm 3 Other values ​​within the range of / g. The pore volume of a porous material refers to the total volume of pores per unit mass of material. An appropriate pore volume can provide an efficient transport path for lithium ions, thereby improving lithium ion insertion / extraction kinetics and enhancing battery charge / discharge performance.

[0069] In some embodiments, the specific surface area of ​​the porous material is 100 m². 2 / g~450m 2 / g. For example, the specific surface area of ​​the porous material can be 100m². 2 / g, 120m 2 / g, 140m 2 / g, 150m 2 / g、160m 2 / g、180m 2 / g、200m 2 / g、220m 2 / g、240m 2 / g、250m 2 / g、260m 2 / g、280m 2 / g、300m 2 / g、320m 2 / g、340m 2 / g, 350m 2 / g、360m 2 / g、380m 2 / g、400m 2 / g、420m 2 / g、440m 2 / g、450m 2 / g, or 100m 2 / g~450m 2Other values ​​within the / g range. An appropriate specific surface area can increase the contact area between the porous material and the first coating layer, which is beneficial to improving the coating uniformity of the first coating layer.

[0070] In some implementations, the porous material includes porous silicon material.

[0071] In some embodiments, the porous material includes a porous silicon material, wherein the mass content of silicon in the negative electrode material is 50% to 80%. Exemplarily, the mass content of silicon in the negative electrode material can be 50%, 52%, 54%, 55%, 56%, 58%, 60%, 62%, 64%, 65%, 66%, 68%, 70%, 72%, 74%, 75%, 76%, 78%, 80%, or other values ​​within the range of 50% to 80%.

[0072] In other embodiments, the aforementioned porous silicon material may include at least one of elemental silicon, silicon oxide, and silicates.

[0073] In some embodiments, the porous silicon material may include elemental silicon, including amorphous silicon, crystalline silicon, or a composite of crystalline and amorphous silicon. For example, the silicon material may include amorphous silicon, which expands isotropically during lithium intercalation, reducing pore collapse in the negative electrode material, suppressing rapid capacity decay, and improving the lithium intercalation cycle performance of the negative electrode material.

[0074] In some embodiments, the porous silicon material may include silicon oxide, which comprises silicon and oxygen elements, wherein the molar ratio x of oxygen and silicon satisfies 0 < x ≤ 2. In some embodiments, the general chemical formula of the silicon oxide is SiOx, where 0 < x ≤ 2. Specifically, SiOx may specifically be SiO 0.5 SiO 0.7 SiO 0.9 SiO, SiO 1.2 SiO 1.5 SiO 1.8 SiO 1.9 SiO2, etc., are not limited here. Silicon oxides can be represented by the general formula SiOx (0 < x ≤ 2), which can be a material formed by silicon dispersed in SiO2; or it can be a material with tetrahedral structural units, in which silicon atoms are located at the center of the tetrahedral structural units, and oxygen atoms and / or silicon atoms are located at the four vertices of the tetrahedral structural units.

[0075] In some embodiments, the purity of porous silicon materials can be greater than or equal to 99%. High-purity silicon materials are more conducive to Li-Si alloying with lithium, thereby improving the cycle performance of lithium-ion batteries prepared from negative electrode materials.

[0076] In some embodiments, the grain size of the porous silicon material on the (111) crystal plane is less than or equal to 10 nm. For example, the grain size of the silicon material on the (111) crystal plane can be 0 nm, 1 nm, 2.5 nm, 3 nm, 3.7 nm, 3.8 nm, 3.9 nm, 4.1 nm, 4.2 nm, 4.9 nm, 5.5 nm, 7 nm, 8 nm, 9 nm, 10 nm, or any value within the range of any two of the above values. The grain size of the silicon material on the (111) crystal plane is calculated by X-ray diffraction analysis combined with the Scherrer equation. This size being within the above range indicates that the silicon-containing grains in the negative electrode material maintain a relatively stable size during charge and discharge, and will not grow significantly, which is beneficial to maintaining the cycle stability of the resulting secondary battery. When the calculated grain size of the silicon material on the (111) crystal plane is 0 nm, it indicates that the silicon material is amorphous silicon, that is, crystalline silicon does not exist.

[0077] In a second aspect, this application also provides a method for preparing a negative electrode material to obtain a negative electrode material having the aforementioned characteristics. The following will be combined with... Figure 2 An illustrative example is provided.

[0078] Figure 2 An exemplary flowchart illustrating a method for preparing a negative electrode material according to some embodiments of this application is shown. Figure 2 As shown, the preparation method 200 may include: in step S201, a mixture of porous material and transition metal salt solution is subjected to hydrothermal reaction to obtain intermediate material, wherein the concentration of transition metal salt solution is 0.5 mol / L to 6 mol / L, and the hydrothermal reaction time is 1 h to 4 h; in step S202, a nitrogen source is introduced into the intermediate material to perform nitriding treatment to obtain a negative electrode material coated with a first coating layer.

[0079] A hydrothermal reaction of a mixture of porous material and a transition metal salt solution yields an intermediate material with a transition metal hydroxide layer coated on its surface. Here, the hydrothermal reaction refers to a reaction in which the porous material is placed in a transition metal salt solution, and the temperature of the solution is controlled. In some embodiments, the hydrothermal reaction temperature can be between 120°C and 150°C, for example, 120°C, 125°C, 130°C, 135°C, 140°C, 145°C, 150°C, or other values ​​within the range of 120°C to 150°C.

[0080] In some embodiments, the average particle size of the porous material is 1 μm to 20 μm. Exemplarily, the average particle size of the porous material can be 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, 20 μm, etc., or other values ​​within the range of 1 μm to 20 μm.

[0081] In some embodiments, the average pore size of the porous material is 2 nm to 200 nm. An appropriate pore size provides an effective transport path for lithium ions, thereby improving lithium ion insertion / extraction kinetics and enhancing battery charge / discharge performance. Conversely, excessively small pore sizes may restrict lithium ion transport, leading to increased lithium ion diffusion resistance during charge / discharge and thus reducing the battery's rate performance. Excessively large pore sizes may reduce the structural stability of the negative electrode material, making it prone to breakage and pulverization during charge / discharge, thus affecting the battery's cycle life.

[0082] In other embodiments, the volume ratio of mesopores to macropores in the porous material is 1 to 10. Exemplarily, this volume ratio can be 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, or other values ​​within the range of 1 to 10. Generally, pores with a diameter of 2 nanometers to 50 nanometers (nm) are called mesopores, while pores larger than 50 nanometers are called macropores. A mesopore to macropore volume ratio in the range of 1 to 10 in porous materials can balance the requirements of lithium-ion transport, electrolyte-electrode contact, volume expansion buffering, and lithium storage sites, thereby optimizing the electrochemical performance of the anode material.

[0083] When the volume ratio of mesopores to macropores in a porous material is less than 1, it means that the volume of macropores is dominant. This may reduce the structural stability of the negative electrode material, making it prone to breakage and cracking during the pressing process when the negative electrode material is made into an electrode sheet, resulting in poor processing performance. When the volume ratio of mesopores to macropores in a porous material is greater than 10, it means that the volume of mesopores is too large, which may restrict the transport of lithium ions. Because the pore size of mesopores is small, it leads to increased resistance to lithium ion diffusion during charging and discharging, thereby reducing the rate performance of the battery.

[0084] In some other embodiments, the pore volume of the porous material is 0.1 cm³. 3 / g~0.8cm 3 / g. For example, the pore volume of the porous material can be 0.1 cm³. 3 / g, 0.15cm 3 / g, 0.2cm 3 / g, 0.25cm3 / g, 0.3cm 3 / g, 0.35cm 3 / g, 0.4cm 3 / g, 0.45cm 3 / g, 0.5cm 3 / g, 0.55cm 3 / g, 0.6cm 3 / g, 0.65cm 3 / g, 0.7cm 3 / g, 0.75cm 3 / g, 0.8cm 3 / g, or 0.1cm 3 / g~0.8cm 3 Other values ​​within the range of / g. The pore volume of a porous material refers to the total volume of pores per unit mass of material. An appropriate pore volume can provide an efficient transport path for lithium ions, thereby improving lithium ion insertion / extraction kinetics and enhancing battery charge / discharge performance.

[0085] In some embodiments, the specific surface area of ​​the porous material is 100 m². 2 / g~450m 2 / g. For example, the specific surface area of ​​the porous material can be 100m². 2 / g, 120m 2 / g, 140m 2 / g, 150m 2 / g、160m 2 / g、180m 2 / g、200m 2 / g、220m 2 / g、240m 2 / g、250m 2 / g、260m 2 / g、280m 2 / g、300m 2 / g、320m 2 / g、340m 2 / g, 350m 2 / g、360m 2 / g、380m 2 / g、400m 2 / g、420m 2 / g、440m 2 / g、450m 2 / g, or 100m 2 / g~450m 2Other values ​​within the / g range. An appropriate specific surface area can increase the contact area between the porous material and the first coating layer, which is beneficial to improving the coating uniformity of the first coating layer.

[0086] In other embodiments, the transition metal salt solution may include at least one of the following: metatitanic acid solution, titanium tetrachloride solution, sodium metavanadate solution, sodium tungstate solution, ammonium metatungstate solution, sodium molybdate solution, ammonium molybdate solution, zirconium chloride solution, chromium chloride solution, tantalum chloride solution, niobium oxalate solution, hafnium tetrachloride solution, and manganese chloride solution. Exemplarily, the concentration of the transition metal salt solution may be 0.5 mol / L, 1.0 mol / L, 1.5 mol / L, 2.0 mol / L, 2.5 mol / L, 3.0 mol / L, 3.5 mol / L, 4.0 mol / L, 4.5 mol / L, 5.0 mol / L, 5.5 mol / L, 6 mol / L, or other values ​​within the range of 0.5 mol / L to 6 mol / L. For example, the hydrothermal reaction time can be 1h, 1.2h, 1.4h, 1.6h, 1.8h, 2h, 2.2h, 2.4h, 2.6h, 2.8h, 3h, 3.2h, 3.4h, 3.6h, 3.8h, 4h, or other values ​​within the range of 1h to 4h.

[0087] The thickness of the first coating layer can be controlled by adjusting the concentration of the transition metal salt solution and the hydrothermal time. Specifically, controlling the concentration of the transition metal salt solution within the range of 0.5 mol / L to 6 mol / L and the hydrothermal time within the range of 1 h to 4 h allows the porous material to react fully with the transition metal salt solution, forming a uniform, appropriately thick, and structurally stable transition metal hydroxide layer on the surface of the porous material. This layer is then transformed into a first coating layer (transition metal nitride) with ideal thickness and performance after subsequent nitriding treatment. Appropriate concentration and hydrothermal time allow for precise control of the growth rate and time of the coating layer, ensuring the consistency and stability of the surface structure of the anode material, and enabling the anode material to possess good resistance to volume expansion and electrochemical performance.

[0088] If the concentration of the transition metal salt solution is too low and / or the hydrothermal time is too short, the hydrothermal reaction may be incomplete, resulting in an insufficiently thin transition metal hydroxide layer. This leads to an inadequate first coating layer, which cannot effectively protect the porous material and affects the performance of the anode material. Conversely, if the concentration of the transition metal salt solution is too high and / or the hydrothermal time is too long, the hydrothermal reaction may be too vigorous, making it difficult to control the growth of the first coating layer. This can easily result in uneven coating and an excessively thick first coating layer, affecting the quality and performance stability of the anode material.

[0089] Further, after obtaining the intermediate material in step S201, step S202 can be performed, in which the intermediate material is placed in a reaction vessel such as a rotary kiln, and a nitrogen source is introduced into the intermediate material to perform nitriding treatment, thereby obtaining a negative electrode material coated with a first coating layer. After nitriding treatment, the first coating layer may include a transition metal nitride. In some embodiments, the nitrogen source may include a gas such as ammonia.

[0090] In other embodiments, the nitriding temperature in step S202 can be controlled between 600°C and 800°C, for example, 600°C, 610°C, 620°C, 630°C, 640°C, 650°C, 660°C, 670°C, 680°C, 690°C, 700°C, 710°C, 720°C, 730°C, 740°C, 750°C, 760°C, 770°C, 780°C, 790°C, 800°C, or other values ​​within the range of 600°C to 800°C.

[0091] In some other embodiments, the nitriding time in step S202 can be controlled to be 1h to 3h, for example 1h, 1.2h, 1.4h, 1.6h, 1.8h, 2h, 2.2h, 2.4h, 2.6h, 2.8h, 3h, or other values ​​within the range of 1h to 3h.

[0092] The above method involves controlling the concentration and hydrothermal time of the transition metal salt solution during the hydrothermal reaction to form a transition metal hydroxide layer on the surface of a porous material. This transition metal hydroxide layer is then transformed into a first transition metal nitride coating layer during the subsequent nitriding process. This preparation method allows for precise control of the formation and growth of the first coating layer, ensuring the quality and performance stability of the anode material.

[0093] In some embodiments, the porous material comprises a porous silicon material. In other embodiments, the porous silicon material may comprise a silicon oxide, which may comprise silicon and oxygen, wherein the molar ratio x of oxygen and silicon satisfies 0 < x < 2. In still other embodiments, the silicon oxide may comprise a mixture of elemental silicon and silicon oxide.

[0094] The aforementioned porous material can be directly used from existing materials with a porosity in the range of 10% to 60% (preferably, 20% to 40%), or it can be prepared through the following steps. An exemplary description will follow.

[0095] In some embodiments, prior to the hydrothermal reaction in step S201, the preparation method 200 may further include: heat-treating the matrix precursor to obtain a matrix intermediate; mixing the matrix intermediate with a hydrofluoric acid solution to etch the matrix intermediate to obtain a porous material, wherein the concentration of the hydrofluoric acid solution is 0.5 mol / L to 4 mol / L, and the etching time is 1 h to 3 h.

[0096] By heat-treating and hydrofluoric acid etching the substrate precursor, the pore structure and morphology of porous materials can be controlled, providing a suitable substrate for subsequent coating processes and thus affecting the performance of the final anode material. In some embodiments, the substrate precursor may include silicon suboxide, which can be at the micrometer scale. By heat-treating the silicon suboxide, a disproportionation reaction can be performed, causing the substrate precursor to form a silicon oxide satisfying the general chemical formula SiOx (0 < x < 2).

[0097] In other embodiments, the heat treatment temperature for heat-treating the matrix precursor can be 800°C to 1100°C, and the heat treatment time can be 4 hours to 8 hours. For example, the heat treatment temperature can be 800°C, 850°C, 900°C, 950°C, 1000°C, 1050°C, 1100°C, or other values ​​within the range of 800°C to 1100°C. For example, the heat treatment time can be 4 hours, 4.5 hours, 5 hours, 5.5 hours, 6 hours, 6.5 hours, 7 hours, 7.5 hours, 8 hours, or other values ​​within the range of 4 hours to 8 hours.

[0098] For example, the concentration of the hydrofluoric acid solution can be 0.5 mol / L, 1.0 mol / L, 1.5 mol / L, 2.0 mol / L, 2.5 mol / L, 3.0 mol / L, 3.5 mol / L, 4 mol / L, or other values ​​within the range of 0.5 mol / L to 4 mol / L. For example, the etching time can be 1 h, 1.5 h, 2 h, 2.5 h, 3 h, or other values ​​within the range of 1 h to 3 h.

[0099] By controlling the concentration of hydrofluoric acid solution and the etching time, the porosity of porous materials can be adjusted, thereby controlling the porosity of anode materials. By controlling the concentration of hydrofluoric acid solution within the range of 0.5 mol / L to 4 mol / L, the matrix intermediate can be moderately etched, forming a porous material with an ideal pore structure. Appropriate concentrations can regulate the porosity, pore size, and distribution of the porous material, meeting the requirements of anode materials for buffering volume expansion and providing lithium storage sites, thus improving the overall performance of the anode material.

[0100] If the concentration of the hydrofluoric acid solution is below 0.5 mol / L, the etching effect is too weak to form sufficient pores, resulting in excessively low porosity of the porous material. This inadequately buffers volume expansion and affects battery performance. If the concentration of the hydrofluoric acid solution exceeds 4 mol / L, the etching effect is too strong, potentially causing excessive damage to the material structure. This results in excessively large average pore size and high porosity, reducing the structural strength of the material and affecting the cycle stability of the battery.

[0101] By controlling the etching time within the range of 1 to 3 hours, it is possible to synergize with the concentration of hydrofluoric acid solution to more precisely control the pore structure of the porous material. A suitable etching time ensures that the formed porous material has appropriate porosity, pore size distribution, and specific surface area, providing a good matrix for subsequent coating processes and contributing to improved overall performance of the anode material.

[0102] If the etching process takes less than 1 hour, it may result in insufficient etching, failing to form an ideal pore structure and leading to poor performance of the porous material. If the etching time exceeds 3 hours, it may result in over-etching, damaging the structure of the porous material, reducing its mechanical strength and stability, and thus affecting battery performance.

[0103] By preparing porous materials using the above method, porous materials that meet the characteristics of porosity, pore volume, pore size range, and volume ratio of mesopores to macropores described above can be obtained, which helps to obtain anode materials that satisfy 5≤P×H≤60 in subsequent coating steps.

[0104] Furthermore, in some other embodiments, the preparation method 200 may further include: performing a second coating treatment on the negative electrode material coated with the first coating layer to obtain a negative electrode material including the second coating layer. The second coating treatment can further optimize the performance of the negative electrode material. Depending on the composition of the second coating layer and the processing technology, the conductivity, stability, etc., of the negative electrode material can be improved to meet the needs of different application scenarios for negative electrode materials. An exemplary description will follow.

[0105] In some embodiments, the second coating treatment may include a carbon coating treatment to obtain a negative electrode material with a carbon-coated second coating layer. In other embodiments, after introducing a nitrogen source for nitriding treatment in step S202, a carbon source may be introduced for the second coating treatment. In still other embodiments, the carbon source may include at least one of gases such as methane, ethane, acetylene, ethylene, propane, and propylene. In some embodiments, the second coating treatment may include a chemical vapor deposition thermal treatment.

[0106] In some embodiments, the coating temperature of the second coating treatment can be controlled to be between 600℃ and 800℃, for example, 600℃, 610℃, 620℃, 630℃, 640℃, 650℃, 660℃, 670℃, 680℃, 690℃, 700℃, 710℃, 720℃, 730℃, 740℃, 750℃, 760℃, 770℃, 780℃, 790℃, 800℃, or other values ​​within the range of 600℃ to 800℃. In other embodiments, the coating time of the second coating treatment can be controlled to be between 1 hour and 3 hours, for example, 1 hour, 1.2 hours, 1.4 hours, 1.6 hours, 1.8 hours, 2 hours, 2.2 hours, 2.4 hours, 2.6 hours, 2.8 hours, 3 hours, or other values ​​within the range of 1 hour to 3 hours.

[0107] The thickness of the second coating layer can be controlled by adjusting the coating temperature and time. By controlling the appropriate coating temperature and time, a negative electrode material with a suitable second coating layer thickness can be obtained. A carbon coating layer of suitable thickness is beneficial for improving the conductivity of the negative electrode material, increasing its structural strength, reducing side reactions, and improving the battery's cycle performance.

[0108] In yet another aspect, this application provides a secondary battery comprising the negative electrode material described in any one of the preceding first aspects of this application, or according to the foregoing combination. Figure 2 The described preparation method yields a negative electrode material. One embodiment of this application provides a secondary battery (such as a lithium-ion battery, sodium-ion battery, etc.) including a casing, an electrode assembly, and an electrolyte / electrolyte. Both the electrode assembly and the electrolyte / electrolyte are located within the casing. The casing can be a packaging bag encapsulated with an encapsulation film (such as an aluminum-plastic film), for example, a pouch battery. In other embodiments, the secondary battery can also be a steel-cased battery, an aluminum-cased battery, etc. The secondary battery of this application embodiment also includes, for example... Figure 1 The electrode components shown, such as the positive electrode and the separator, will not be described in detail here.

[0109] Examples and comparative examples:

[0110] To better understand the performance of the negative electrode material and its preparation method according to the embodiments of this application, specific examples will be described below. Several comparative examples are also provided below to further illustrate the advantages of the negative electrode material according to the embodiments of this application.

[0111] Example 1:

[0112] Step 1) Place 100g of silicon suboxide with an average particle size of 3μm in a box furnace, introduce nitrogen (inert gas atmosphere), and heat to 900℃ at a heating rate of 3℃ / min to heat treat the silicon suboxide for 4 hours to obtain a matrix intermediate; after the heat treatment, cool to room temperature, mix the matrix intermediate with 500mL of 2mol / L hydrofluoric acid solution to etch the matrix intermediate for 1 hour, and then wash and vacuum dry the product to obtain a porous material.

[0113] Step 2) Mix the porous material with a 2 mol / L metatitanic acid solution and stir for 1 hour. Transfer the mixture to a reactor for hydrothermal reaction. The hydrothermal reaction temperature is controlled at 120℃ and the hydrothermal time is 2 hours to obtain the intermediate material.

[0114] Step 3) The intermediate material is placed in a rotary kiln for nitriding treatment, specifically including: heating to 700°C at a heating rate of 5°C / min (i.e., controlling the nitriding temperature to 700°C), then introducing ammonia gas at a flow rate of 0.5L / min, and controlling the nitriding time to 1 hour to obtain a negative electrode material including the first coating layer.

[0115] Step 4) Introduce propane gas at a rate of 2 L / min, maintain the coating temperature at 700℃, and control the coating time for 2 hours to perform the second coating treatment. After the second coating treatment, cool down to room temperature to obtain the negative electrode material coated with the second coating layer.

[0116] Examples 2-10: The only difference from Example 1 is that in step 2), the metatitanic acid solution is replaced with sodium metavanadate solution, sodium tungstate solution, sodium molybdate solution, zirconium chloride solution, chromium chloride solution, tantalum chloride solution, niobium oxalate solution, hafnium tetrachloride solution, and manganese chloride solution, respectively.

[0117] Example 11: The only difference from Example 1 is that in step 1), the concentration of hydrofluoric acid solution is 0.5 mol / L; in step 2), the concentration of metatitanic acid solution is 0.5 mol / L, and the hydrothermal time is 4 hours.

[0118] Example 12: The only difference from Example 1 is that in step 1), the concentration of hydrofluoric acid solution is 3.0 mol / L; in step 2), the concentration of metatitanic acid solution is 3.0 mol / L, and the hydrothermal time is 1 hour.

[0119] Example 13: The only difference from Example 1 is that in step 1), the concentration of hydrofluoric acid solution is 4.0 mol / L and the etching time is 3 hours.

[0120] Example 14: The only difference from Example 1 is that in step 2), the concentration of the metatitanic acid solution is 6.0 mol / L and the hydrothermal time is 4 hours.

[0121] Example 15: The only difference from Example 1 is that in step 1), the concentration of hydrofluoric acid solution is 3.0 mol / L and the etching time is 1.5 hours; in step 2), the concentration of metatitanic acid solution is 3.0 mol / L and the hydrothermal time is 3 hours.

[0122] Example 16: The only difference from Example 1 is that step 4 is omitted.

[0123] Example 17: The only difference from Example 1 is that in step 1), the concentration of hydrofluoric acid solution is 0.3 mol / L and the etching time is 0.5 hours; in step 2), the concentration of metatitanic acid solution is 3.0 mol / L and the hydrothermal time is 1 hour.

[0124] Example 18: The only difference from Example 1 is that in step 1), the concentration of hydrofluoric acid solution is 4.5 mol / L and the etching time is 3 hours.

[0125] Example 19: The only difference from Example 1 is that in step 1), the concentration of hydrofluoric acid solution is 4 mol / L and the etching time is 2 hours; in step 2), the concentration of metatitanic acid solution is 0.4 mol / L and the hydrothermal time is 0.5 hours.

[0126] Example 20: The only difference from Example 1 is that in step 1), the concentration of hydrofluoric acid solution is 0.5 mol / L and the etching time is 1 hour; in step 2), the concentration of metatitanic acid solution is 6.3 mol / L and the hydrothermal time is 4 hours.

[0127] Example 21: The only difference from Example 1 is that in step 1), the concentration of hydrofluoric acid solution is 0.3 mol / L and the etching time is 0.5 hours; in step 2), the concentration of metatitanic acid solution is 6.3 mol / L and the hydrothermal time is 4 hours.

[0128] Example 22: The only difference from Example 1 is that in step 1), the concentration of hydrofluoric acid solution is 0.3 mol / L and the etching time is 0.5 hours; in step 2), the concentration of metatitanic acid solution is 0.4 mol / L and the hydrothermal time is 0.5 hours.

[0129] Comparative Example 1: The only difference from Example 1 is that steps 2) and 3) are not performed, and in step 4), after heating to 700°C at a heating rate of 5°C / min, propane gas is introduced at a rate of 2L / min.

[0130] Comparative Example 2: The only difference from Example 1 is that in step 1), the concentration of hydrofluoric acid solution is 0.3 mol / L and the etching time is 0.5 hours; in step 2), the concentration of metatitanic acid solution is 0.4 mol / L and the hydrothermal time is 0.5 hours.

[0131] Comparative Example 3: The only difference from Example 1 is that in step 1), the concentration of hydrofluoric acid solution is 4.5 mol / L and the etching time is 3.0 hours; in step 2), the concentration of metatitanic acid solution is 6.5 mol / L and the hydrothermal time is 4 hours.

[0132] Comparative Example 4: The only difference from Example 1 is that in step 1), the concentration of hydrofluoric acid solution is 4.0 mol / L and the etching time is 2.0 hours; in step 2), the concentration of metatitanic acid solution is 0.3 mol / L and the hydrothermal time is 0.5 hours.

[0133] Comparative Example 5: The only difference from Example 1 is that in step 1) and step 2), the concentration of the metatitanic acid solution is 6.3 mol / L and the hydrothermal time is 4 hours.

[0134] Comparative Example 6: The only difference from Example 1 is that in step 1), the concentration of the hydrofluoric acid solution is 0.4 mol / L and the etching time is 0.5 hours.

[0135] Comparative Example 7: The only difference from Example 1 is that in step 1), the concentration of the hydrofluoric acid solution is 5.0 mol / L and the etching time is 3.0 hours.

[0136] Performance testing methods:

[0137] This application also conducted the following performance tests on the anode materials prepared in the above embodiments and comparative examples:

[0138] (1) Test method for particle size of negative electrode material:

[0139] The particle size distribution range of the negative electrode material was tested using a Malvern laser particle size analyzer (Mastersizer 3000). The cumulative particle size distribution based on volume was determined using laser diffraction. The median particle size D50 was obtained by referring to GB / T 19077.1-2008 "Particle Size Analysis - Laser Diffraction - Part 1: General Rules" or the equipment manual. D50 represents the particle size corresponding to 50% of the cumulative particle size distribution by volume.

[0140] (2) Test method for specific surface area of ​​negative electrode material:

[0141] After determining the amount of adsorbed gas on the solid surface at different relative pressures under constant temperature and low temperature conditions, the monolayer adsorption capacity of the sample was calculated based on the Brownnor-Etter-Taylor adsorption theory and its formula (BET formula), thereby calculating the specific surface area of ​​the material. Measurements were performed according to GB / T 19587-2004 "Determination of Specific Surface Area of ​​Solid Substances by Gas Adsorption BET Method" or the equipment instruction manual. In this application, a specific surface area and pore size analyzer (McASAP2460-2) was used for measurement, and the adsorbed gas was N2.

[0142] (3) Methods for testing the pore volume of negative electrode materials and porous materials:

[0143] The total pore volume was calculated using a specific gravity and pore size analyzer (McASAP2460-2) by analyzing the adsorption amount in the high-pressure region (P / P0 close to 1) through adsorption isotherms. The test procedure included: 1. Measuring the full-range adsorption isotherm (P / P0 from 0 to 0.99); 2. When P / P0≈0.99, assuming the pores were filled with liquid adsorbate, the adsorption amount was converted into pore volume (e.g., ...). Its liquid density is 0.808 g / cm³. 3 ).

[0144] (4) Methods for testing the average pore size of negative electrode materials and porous materials:

[0145] A specific gravity meter and pore size analyzer (McASAP2460-2) were used. Based on capillary condensation theory, the pore size distribution was calculated through desorption isotherms, and then the average pore size was obtained by volume weighted averaging. The testing process included: 1. Measuring the desorption isotherms; 2. Assuming the pores were cylindrical, the pore size distribution was calculated using the Kelvin equation.

[0146] (5) Compaction density test of negative electrode material:

[0147] The CARVER 4350.22 powder compaction density tester from McNaught (USA) was used. A sample of a specified mass was placed in a mold and a pressure of 1.0T was applied. After holding the pressure for 30 seconds, the pressure was released and the thickness was measured. The compaction density was then calculated. The specific operation method is to place a certain mass of powder sample in a metal sleeve and hold it under a certain pressure for a certain time. The ratio of the mass of the sample to the volume after compaction is then calculated.

[0148] (6) Testing of grain size of silicon material on the (111) crystal plane:

[0149] The XRD pattern of the sample was measured by an X-ray diffractometer. The half-peak height and width of the diffraction peaks on the (111) crystal surface of the sample and the corresponding Bragg angle were obtained by the Jade software. The grain size on the (111) crystal surface of the silicon material was calculated by the Scherrer formula D=Kγ / B cosθ.

[0150] (7) Porosity test of negative electrode material:

[0151] Mercury intrusion porosimetry (MIP) is a method for calculating porosity by measuring the pressure change of mercury within the pores of a material. This method uses a high-performance, fully automated mercury intrusion porosimetry instrument, such as the AutoPore IV 9500 from Micron Instruments, to inject mercury into the pores of the material. Based on the changes in mercury volume and pressure, the porosity and pore distribution can be calculated.

[0152] (8) Electrochemical performance testing methods:

[0153] The negative electrode materials prepared in each embodiment and comparative example were mixed with a conductive agent (Super P, conductive carbon black) and a binder (PAA, polyacrylic acid) in a solvent at a mass ratio of 90:5:5. The resulting slurry was coated onto a copper foil current collector, dried, and pressed to obtain negative electrode sheets for later use. The negative electrode sheets were then used to assemble CR2025 coin cells, and their electrochemical performance was tested using a blue dot test system. Battery assembly was performed in an argon glove box, using lithium metal sheets as the positive electrode, a 1 mol / L LiPF6 electrolyte (LiPF6 dissolved in a 1:1 volume ratio mixture of ethylene carbonate (EC) and dimethyl carbonate (DMC), and a polyethylene or polypropylene composite microporous membrane as the separator. The capacity and first-cycle efficiency of the materials were tested at a current density of 0.1C, and the 50-cycle retention rate and volume expansion rate were tested at a current density of 1C. When testing the volume expansion rate, the thickness of the battery electrode sheets was measured using a micrometer.

[0154] (9) Mass content test of the first coating layer:

[0155] The negative electrode material was analyzed using X-ray diffraction (XRD). In the XRD image, the metal elements in the negative electrode material of this application embodiment mainly showed as transition metal nitride peaks, indicating that the metal elements in the negative electrode material mainly exist in the form of transition metal nitrides. Therefore, the content of transition metal nitrides can be calculated by measuring the content of metal elements by methods such as ICP, that is, the mass content of the first coating layer in the negative electrode material can be obtained.

[0156] (10) Test of carbon content:

[0157] The carbon content in the anode material was determined by analyzing and measuring the carbon element using an infrared carbon-sulfur analyzer.

[0158] (11) Test of silicon content:

[0159] Using Nanyang Xinyu's SA2-9-17TP box-type atmosphere furnace, the negative electrode material was first burned in an oxygen atmosphere, causing the silicon in the sample to react into silicon dioxide and the carbon to burn into carbon dioxide and be discharged. Then, the burning residue was placed in a nitric acid solution to react fully, remove the metal, wash the residue, dry it, weigh it, and calculate the mass percentage of silicon.

[0160] (12) Testing of coating thickness:

[0161] The material was cross-sectioned using FIB-SEM equipment, and the electron microscope image of the negative electrode material was obtained by cross-section SEM scanning. Ten particles were randomly selected, and the coating thickness was measured at ten random locations on each particle. The average thickness of the first coating layer and the second coating layer was measured.

[0162] To facilitate the description of the differences between the above embodiments and comparative examples, as well as the test results of each embodiment and comparative example, the following will refer to Tables 1 and 2. Figure 3 and Figure 4 Further explanation is provided. Table 1 shows the different preparation conditions of each embodiment and comparative example compared to Example 1; Table 2 shows the test results of the negative electrode material samples prepared in each embodiment and comparative example. Figure 3 The XRD pattern of the negative electrode material of Example 1 is shown; Figure 4 An SEM image of the negative electrode material of Example 1 is shown.

[0163] Table 1:

[0164]

[0165]

[0166] Table 2:

[0167]

[0168]

[0169]

[0170] The data in Tables 1 and 2 above show that:

[0171] (1) As can be seen from Tables 1 and 2, Examples 1 to 22 were prepared under different conditions such as different transition metal salt solutions, different hydrofluoric acid solution concentrations, different etching times, different transition metal salt solution concentrations, and different hydrothermal times. The resulting negative electrode materials all satisfy 5≤P×H≤60. The resulting negative electrode sheets can maintain a low volume expansion rate after charge-discharge cycles, and the resulting secondary batteries have high capacity, initial coulombic efficiency, and cycle stability.

[0172] (2) As can be seen from Tables 1 and 2, compared with the negative electrode material of Comparative Example 1 without the first coating layer, the porous material of Example 1 has a transition metal nitride coating on its core surface, and the negative electrode material of Example 1 satisfies 5≤P×H≤60. The results show that the volume expansion rate of the negative electrode material of Example 1 is significantly reduced, indicating that the expansion resistance of the negative electrode material coated with the first coating layer is significantly improved. At the same time, the capacity, first-efficiency, and cycle capacity retention of the negative electrode material of Example 1 are also better than those of Comparative Example 1, indicating that the negative electrode material of Example 1 has superior comprehensive performance.

[0173] (3) From Figure 3 It can be seen that transition metal nitrides are present in the negative electrode material prepared in Example 1. From Figure 4 It can be seen that the negative electrode material prepared in Example 1 has two coating layers: a first coating layer and a second coating layer.

[0174] (4) As can be seen from Table 2, Example 16 only has the first coating layer, while Comparative Example 1 only has the second coating layer. In comparison, the capacity, 50-cycle capacity retention rate and volume expansion rate of the negative electrode material of Example 16 are better than those of Comparative Example 1. This shows that the presence of the first coating layer can significantly improve the cycle stability and expansion resistance of the negative electrode material, making the negative electrode material have better overall performance.

[0175] (5) As can be seen from Tables 1 and 2, the results of Examples 1 to 22 show that when the negative electrode material 5≤P×H≤60, the volume expansion rate of the negative electrode material generally decreases with the increase of the P×H value, indicating that the volume expansion resistance of the negative electrode material increases with the increase of the P×H value.

[0176] (6) As can be seen from Tables 1 and 2, in Comparative Example 2, the negative electrode material P×H = 0.72 < 5, while in Comparative Example 3, the negative electrode material P×H = 237.36 > 60. The negative electrode material in Comparative Example 2 has too small a porosity, too small a volume change buffer zone, and a thin transition metal nitride layer, resulting in low structural strength, poor resistance to volume expansion, and poor cycle stability. Although the negative electrode material in Comparative Example 3 has a larger porosity and a thicker transition metal nitride layer, resulting in strong resistance to volume expansion and a smaller volume expansion rate, the excessively thick transition metal nitride layer makes lithium ion insertion / extraction difficult, leading to poor capacity and first-cycle efficiency.

[0177] (7) As can be seen from Tables 1 and 2, Comparative Example 4 used a transition metal salt solution with too low a concentration, resulting in an excessively thin first coating layer, which in turn affected the P×H value of the negative electrode material, making P×H = 4.53 < 5. Therefore, its effect on improving the volume expansion resistance and cycle stability of the negative electrode material was limited. Comparative Example 5 used a transition metal salt solution with too high a concentration, resulting in an excessively thick first coating layer, which in turn affected the P×H value of the negative electrode material, making P×H = 62.26 > 60. While a thicker first coating layer is beneficial for improving the volume expansion resistance and cycle stability of the negative electrode material, it also leads to poor lithium storage performance, thus affecting the capacity and first-time efficiency of the negative electrode material. Therefore, a P×H value in the range of 5 to 60, with appropriate porosity and a suitable first coating layer thickness, is beneficial for improving the overall performance of the negative electrode material.

[0178] (8) As can be seen from Tables 1 and 2, Comparative Example 6 used a hydrofluoric acid solution with too low a concentration, resulting in too small a porosity, which in turn affected the P×H value of the negative electrode material, making P×H = 4.4 < 5. The small porosity leads to a small buffer area for the volume change of the negative electrode material particles, resulting in poor resistance to volume expansion. Comparative Example 7 used a hydrofluoric acid solution with too high a concentration, resulting in too large a porosity, which in turn affected the P×H value of the negative electrode material, making P×H = 63.7 > 60. Although a larger porosity is beneficial to improving the resistance to volume expansion of the negative electrode material, it reduces the strength of the negative electrode material, which will cause the structure to collapse easily during the lithium insertion / extraction process, thus affecting the cycle stability of the negative electrode material. Therefore, a P×H value in the range of 5 to 60, with appropriate porosity and thickness of the first coating layer, is beneficial to improving the overall performance of the negative electrode material.

[0179] (9) As can be seen from Table 2, the porosity of the negative electrode material in Example 17 is too small, while the porosity of the negative electrode material in Example 18 is too large. Compared with Example 1, the capacity retention rate of Examples 17 and 18 has decreased, while the volume expansion rate has increased. This indicates that a porosity P of 5% to 50% for the negative electrode material is beneficial for further improving the cycle stability and volume expansion resistance of the secondary battery.

[0180] (10) As can be seen from Table 2, the thickness of the first coating layer of the negative electrode material in Example 19 is too small. Compared with Example 1, the capacity retention rate of Example 19 is lower and the volume expansion rate is higher. The thickness of the first coating layer of the negative electrode material in Example 20 is too large. Compared with Example 1, the capacity, first-time efficiency, capacity retention rate, and volume expansion rate of Example 20 are all lower. This shows that although increasing the thickness of the first coating layer is beneficial to further improve the volume expansion resistance of the secondary battery, an excessively thick first coating layer may affect other performance characteristics of the secondary battery. Therefore, a thickness of 20 nm to 400 nm for the first coating layer of the negative electrode material is beneficial to ensuring the overall performance of the secondary battery.

[0181] (11) As can be seen from Table 2, the porosity of the negative electrode material in Example 21 is too small, and the thickness of the first coating layer is too large. Compared with Example 1, the capacity, initial efficiency, and capacity retention rate of Example 21 are all reduced. The thickness of the first coating layer of the negative electrode material in Example 22 is too small. Compared with Example 1, the capacity retention rate of Example 22 is reduced, and the volume expansion rate is increased. This further illustrates that a porosity P of 5% to 50% for the negative electrode material and a thickness of 20 nm to 400 nm for the first coating layer are beneficial to ensuring the overall performance of the secondary battery.

[0182] In summary, the embodiments of this application provide a negative electrode material that satisfies 5≤P×H≤60, achieving a good balance between the negative electrode material's resistance to volume expansion and its electrochemical performance. The reasonable combination of the negative electrode material's porosity and the thickness of the first coating layer provides a better buffer and support structure, while also ensuring relatively smooth lithium ion insertion / extraction channels, maintaining good capacity and first-efficiency performance, and enabling the battery to maintain stable performance during cycling.

[0183] While numerous embodiments of this application have been shown and described herein, it will be apparent to those skilled in the art that such embodiments are provided by way of example only. Many modifications, alterations, and alternatives will arise for those skilled in the art without departing from the spirit and intent of this application. It should be understood that various alternatives to the embodiments of this application described herein may be employed in the practice of this application. The appended claims are intended to define the scope of protection of this application and therefore cover equivalents or alternatives within the scope of these claims.

Claims

1. A negative electrode material, characterized in that, The negative electrode material includes a porous material and a first coating layer, the first coating layer being located on at least a portion of the surface of the porous material, and the negative electrode material satisfies the following: 5≤P×H≤60; Wherein, P represents the porosity of the negative electrode material, and H represents the thickness of the first coating layer.

2. The negative electrode material according to claim 1, characterized in that, The negative electrode material also satisfies at least one of the following characteristics: (1) The porosity P of the negative electrode material is 5% to 50%; (2) The thickness H of the first coating layer is 20nm to 400nm; (3) The first coating layer comprises a transition metal nitride.

3. The negative electrode material according to claim 1 or 2, characterized in that, The first coating layer comprises a transition metal nitride, which includes at least one of titanium nitride, vanadium nitride, tungsten nitride, molybdenum nitride, zirconium nitride, chromium nitride, tantalum nitride, niobium nitride, hafnium nitride, and manganese nitride.

4. The negative electrode material according to claim 1 or 2, characterized in that, The negative electrode material also satisfies at least one of the following characteristics: (1) The porosity P of the negative electrode material is 10% to 30%; (2) The thickness H of the first coating layer is 50nm to 200nm.

5. The negative electrode material according to claim 1 or 2, characterized in that, The negative electrode material further includes a second coating layer, which covers at least a portion of the surface of the first coating layer.

6. The negative electrode material according to claim 5, characterized in that, The negative electrode material also satisfies at least one of the following characteristics: (1) The second coating layer comprises at least one of carbon material, metal oxide and phosphate; (2) The thickness of the second coating layer is 50 nm to 1000 nm; (3) The mass content of the first coating layer in the negative electrode material is 2% to 10%; (4) The second coating layer comprises carbon material, wherein the mass content of carbon element in the negative electrode material is 10% to 40%.

7. The negative electrode material according to claim 1 or 2, characterized in that, The negative electrode material also satisfies at least one of the following characteristics: (1) The median particle size of the negative electrode material is 1 μm to 22 μm; (2) The specific surface area of ​​the negative electrode material is 1m². 2 / g~20m 2 / g; (3) The compaction density of the negative electrode material is 0.5 g / cm³. 3 ~3.0g / cm 3 ; (4) The average pore size of the negative electrode material is 1.5 nm to 35 nm; (5) The total pore volume of the negative electrode material is 0.002 cm³. 3 / g~0.1cm 3 / g.

8. The negative electrode material according to claim 1, characterized in that, The porous material also satisfies at least one of the following characteristics: (1) The average particle size of the porous material is 1 μm to 20 μm; (2) The average pore size of the porous material is 2nm to 200nm; (3) The volume ratio of mesopores to macropores in the porous material is 1 to 10; (4) The pore volume of the porous material is 0.1 cm³. 3 / g~0.8cm 3 / g; (5) The specific surface area of ​​the porous material is 100 m². 2 / g~450m 2 / g.

9. The negative electrode material according to claim 1 or 8, characterized in that, The porous material also satisfies at least one of the following characteristics: (1) The porous material includes porous silicon material, wherein the mass content of silicon element in the negative electrode material is 50% to 80%; (2) The porous silicon material includes at least one of elemental silicon, silicon oxide and silicate; (3) The purity of the porous silicon material is greater than or equal to 99%; (4) The size of the grains on the (111) crystal plane of the porous silicon material is less than or equal to 10 nm.

10. A secondary battery, characterized in that, The secondary battery includes the negative electrode material as described in any one of claims 1-9.